A basic study on incentive pricing for demand response programs based on social welfare maximization. Issue 1 (1st January 2018) - Takano, Hirotaka; Kudo, Asuka; Taoka, Hisao; Ohara, Atsumi
ABSTRACT: Demand response programs (DRs) have been getting more active as one of the effective demand-side management methods (DSMs), which can contribute to the power supply-demand balancing operations in electric power grids. In particular, peak-time-rebate-DR (PTR-DR) is expected to penetrate further because it brings benefit both electric power suppliers and consumers with smaller burden on the consumer-side in comparison with the other DR types. Although several demonstrative field tests on the DRs have been promoted, there is room for discussion yet how to set the appropriate incentive payment for the cooperation of DR requirement from the power suppliers. This paper presents a pricing method of incentive payment in the DRs based on a problem framework of social optimization. In the authors' proposal, decrement of the consumers' comfort, which is caused by the DR cooperation, is converted into the price. That is, the proposed pricing method calculates the negative consumers' surplus as the appropriate incentive payment in the DRs.